CYP2D6 Predicts Plasma Donepezil Concentrations in a Cohort of Thai Patients with Mild to Moderate Dementia - Chamnanphon M; Wainipitapong S; Wiwattarangkul T; Chuchuen P; Nissaipan K; Phaisal W; Tangwongchai S; Sukasem C; Wittayalertpanya S; Gaedigk A; Aniwattanapong D; Chariyavilaskul P (Dove Medical Press, 2020)
Monpat Chamnanphon,1 Sorawit Wainipitapong,2 Teeravut Wiwattarangkul,3 Phenphichcha Chuchuen,2 Kunathip Nissaipan,1,4 Weeraya Phaisal,1,4 Sookjaroen Tangwongchai,2 Chonlaphat Sukasem,5 Supeecha Wittayalertpanya,1,4 Andrea Gaedigk,6 Daruj Aniwattanapong,2 Pajaree Chariyavilaskul1,4 1Clinical Pharmacokinetics and Pharmacogenomics Research Unit, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 2Department of Psychiatry, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 3Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 4Department of Pharmacology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 5Division of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 6Division of Clinical Pharmacology, Toxicology & Therapeutic Innovation, Children’s Mercy Kansas City and School of Medicine, University of Missouri-Kansas City, Kansas City, Missouri, USACorrespondence: Daruj AniwattanapongDepartment of Psychiatry, Faculty of Medicine, Chulalongkorn University, Bangkok, ThailandTel +66 2 256 4298Email daruj.a@chula.ac.thPajaree ChariyavilaskulDepartment of Pharmacology, Faculty of Medicine, Chulalongkorn University, Bangkok, ThailandTel +66 2 256 4481 ext. 3020Email pajaree.l@chula.ac.thPurpose: Donepezil, a drug frequently used to treat dementia, is mainly metabolized by cytochrome P450 2D6 (CYP2D6). This study investigated the relationships between CYP2D6 genotype and activity scores as well as predicted phenotype of plasma donepezil concentrations in 86 Thai dementia participants.Materials and Methods: CYP2D6 was genotyped using bead-chip technology (Luminex xTAG® v.3). Steady-state trough plasma donepezil concentrations were measured using high-performance liquid chromatography.Results: Sixteen genotypes were found but the most frequent genotypes detected among our participants were CYP2D6*10/*10 (27.9%) and *1/*10 (26.7%). One-third of the participants had an activity score of 1.25 which predicted that they were normal metabolizers. The overall median (interquartile range) of plasma donepezil concentration was 51.20 (32.59– 87.24) ng/mL. Normal metabolizers (NMs) had lower plasma donepezil concentrations compared to intermediate metabolizers (IMs) (41.15 (28.44– 67.65) ng/mL vs 61.95 (35.25– 97.00) ng/mL). Multivariate analysis showed that CYP2D6 activity score (r2 = 0.50) and the predicted phenotype (independent of dose) could predict the plasma donepezil concentration (r2 = 0.49).Conclusion: Plasma donepezil concentration in NMs was lower compared to IMs. Additional studies with larger sample size and use of next-generation sequencing as well as its outcomes are warranted to confirm the benefit of using pharmacogenetic-guided treatment for donepezil.Keywords: CYP2D6, Luminex xTAG®, donepezil, dementia, pharmacogenetics